The Effects of Islamic Financial Literacy, Lifestyle and Self-Control on Intention to Use Online Loans: an Extended TAM Approach - Khasanah, Miftakhul; Aulia, Nuraini Intan (IQTISHADIA, 2024)
This research aims to investigate the relationship between lifestyle, self-control, Islamic financial literacy, and intention to use online loans. This research uses quantitative research methods with an exploratory approach. The population in this study were Indonesian citizens aged 17 to 55 years. The number of samples used in this research was 403 respondents. The data collection technique used was distributing questionnaires via Google Form. The research results were analyzed using Smart PLS 3. Attitude is only able to mediate between lifestyle and intention to use online loans, but is not able to mediate the variables of Islamic financial literacy and self-control. However, attitude is the biggest variable that can influence the intention to use online loans. Meanwhile, the intention to use online loans is influenced by Islamic financial literacy, lifestyle, self-control and attitude by 79.9%. Meanwhile, 20.1% was influenced by other factors outside this research model.